Efeitos da infusão de células-tronco mesenquimais sobre o músculo esquelético em modelo de diabetes mellitus - Luna, Genoveva L. Flores (Universidade Federal de São Carlos, 2019)
Aim of the Study: The present study aimed to evaluate the effects of Mesenchymal Stromal Cell (MSCs) transplantation on motor function and collagen organization in type 1 diabetes mellitus rat skeletal muscles. Materials and Methods: Male Wistar rats were randomly assigned to 3 groups: Control (C), Diabetic (DM) and Diabetic treated with MSCs (DM-MSCs). Diabetes was induced by Streptozotocin (50 µg/kg). The MSCs were isolated from tibia and femur bone marrows. Ten weeks after DM induction, DM-MSC group received 4 weekly i.p. injections of MSCs (1 x 106). Ten weeks after MSC transplantation, motor performance was evaluated by the Rota Rod test and the anterior tibial (TA) muscles were collected for morphometric analysis and quantification of collagen by birefringence by polarizing microscopy analysis. Results: Motor performance of the DM group was significantly reduced when compared to the C group and increased significantly in the DM + MSCs group. The TA muscle mass and the muscle fiber cross sectional area were significantly reduced in the DM and DM + MSCs groups compared to the C group. The connective tissue increased in the DM group compared to the C group and decreased in the DM + MSCs group. The percentage of collagen birefringence of the connective tissue of the TA muscle decreased significantly in the DM group when compared to the C group and increased in the DM + MSCs group. Motor performance was positively correlated with collagen birefringence and negatively correlated with percentage of connective tissue. Conclusions: The results indicate that MSCs transplantation improves both motor function and the collagen macromolecular organization of skeletal muscle in type 1 DM.
Effects of mesenquimal stem cell infusion on the skeletal muscle in diabetes mellitus model
Keywords: Diabetes Mellitus; Músculo esquelético; Terapia celular; Matriz extracelular; Colágeno; Skeletal muscle; Cellular therapy; Extracellular matrix; Collagen; CIENCIAS BIOLOGICAS::FISIOLOGIA